Control in competitive sport as exemplified by a women basketball team in the Polish First League - Ozimek, M.; Szmatlan-Gabrys, U.; Gabrys, T.; Stanula, A.; Stanisz, L.; Grabacka-Pietruszka, B.; Majka, J.; Eliasz-Radzikowski, W. (Studia Sportiva, 2017)
This article aims to present elements of control within the selected areas of motor preparation in competitive athletes established at rest and after exercise. Identifying the effect of fatigue on the values of the controlled coefficients allows assessing training effectiveness, comparing athletes for performance, as well as determining the kinetics of oxygen deficit, oxygen debt, oxygen uptake or the level of lactate concentration at different stages of continued exercise. This type of research provides both athletes and their coaches with immediate information on how well the former are prepared and enables the control of training results.